DETERMINANTS BEHIND PUBLIC SERVICE QUALITY: UNPACKING THE ROLE OF EMPLOYEE ENGAGEMENT IN THE NEXUS OF WORK-LIFE BALANCE AND DIGITAL COMPETENCE IN SAMBOJA DISTRICT - Ameliya Bangun; Dirga Lestari; Ariesta Heksarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing demand for responsive, transparent, and technology-based public services has placed government employees in increasingly complex work conditions, where service quality is shaped not only by systems and digital infrastructure but also by employees' work conditions and psychological attachment to their roles. This study aims to analyze the role of employee engagement in mediating the relationship between work-life balance and digital competence on public service quality in the Samboja District Office. A quantitative approach was employed using a survey method involving district-level government employees as respondents. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among variables. The findings indicate that work-life balance and digital competence significantly influence employee engagement, which subsequently contributes to the improvement of public service quality. In addition, employee engagement functions as a mediating variable that strengthens the relationship between both independent variables and service quality. These results suggest that improving public service quality cannot rely solely on enhancing technical capabilities and digital skills but must also consider employees' work-life balance and their level of engagement. Practically, this study provides implications for local governments in designing integrated human resource management policies that simultaneously promote employee well-being, digital competence development, and stronger engagement to achieve sustainable improvements in public service quality.